Azygos Lobe: Prevalence of an Anatomical Variant and Its Recognition among Postgraduate Physicians - Al-Mnayyis, Asma’a (Diagnostics (Basel), 2020)
The right azygos lobe is a rare anatomical variant of the upper lung lobe that can be misdiagnosed as a neoplasm, a lung abscess, or a bulla. The aim of this study was to assess the prevalence of right azygos lobe and to evaluate the ability of postgraduate doctors to correctly identify right azygos lobe. We analyzed a total of 1709 axial thoracic multi-detector computed tomography (CT) images for the presence of an azygos lobe. Additionally, a paper-based survey was distributed among a sample of intern doctors and radiology and surgery residents, asking them to identify the right azygos lobe in a CT image and in an anatomy figure. Results showed that the prevalence of the right azygos lobe in the study sample was 0.88%. Men have more right azygos lobes than women. None of the intern doctors or surgery residents identified the right azygos lobe correctly, whereas more than half (57.1%) of the radiology residents did. Most of the incorrect answers about the CT scan were related to the bronchi (25.0%). The apex of the lung (17.7%) and the superior vena cava (17.7%) were the most common incorrect answers about the anatomy figure. In conclusion, the prevalence of the right azygos lobe in the current study is within the range of previously published literature. More education should be given for the identification of the right azygos lobe during anatomy and clinical teaching.